Health Information and Promotion Media Health Office of North Sumatra Province - Zuhrina Aidha; Nisa Mahfirah Lubis; Nur'ainun Berutu; Surianti Surianti; Suci Yustrianti Marpaung; Rian Atta Nayoan Nasution; Vivi Chairani Harahap (LPPM UIKA Bogor, 2023)
Health promotion media are all means or efforts to display messages or information to be conveyed by communicators, both through print media, electronics (in the form of radio, TV, computers, and so on), and outdoor media, so that the target can increase their knowledge which is then expected to become a change towards positive behavior in the health sector. Health Promotion and Community Empowerment The North Sumatra Provincial Health Office in increasing public knowledge about health and in empowering the community to improve their health status involves the business community and community organizations as well as media dissemination. The purpose of this research was to find out how information media and health promotion are in the Health Office of North Sumatra Province. The research method uses qualitative research with descriptive and peer review methods to direct research to staff who are directly at the North Sumatra Health Office as a source of information about media information in promoting public health who know for sure accurate and factual. In this study, the authors chose informants based on the needs of the authors. The author chose sources from the North Sumatra Health Office. The results of the research are health promotion, namely a form of education that aims to encourage people to behave healthily, and a form of enlightenment, namely by persuasion, persuasion, appeals, invitations, and providing information or awareness about health. Health education or promotion is a behavioral intervention that shapes behavior into good health behavior. Health promotion aims to ensure that the behavior of individuals, groups, or communities has a positive effect on maintaining and improving health. Health media includes print media in the form of leaflets, banners, and posters as well as digital media in the form of social media applications, namely WhatsApp, Facebook, and so on. Through these media the health messages conveyed are interesting and easy to understand so that the target can easily accept the messages conveyed, the media can facilitate the delivery of information, the media can avoid misperceptions, the media can clarify information, and the media can make it easier to understand.